KADAR PROTEIN, TEKSTUR, DAN SIFAT ORGANOLEPTIK COOKIES YANG DISUBSTITUSI TEPUNG GANYONG (Canna edulis) DAN TEPUNG KACANG KEDELAI (Glycine max L.) - Titik Isnaini Lestari; Nurhidajah Nurhidajah; Muhammad Yusuf (Jurnal Pangan dan Gizi, 2018)
Product diversification of ganyong processed is needs to be done to improve the receipt. The addition of soy is intended to increase the levels of protein. This study aimed to get cookies formulations which substituted by ganyong flour and best soy flour based on the levels of protein, texture, and characteristic of organoleptic. This study used randomized design and completely with a factor, randomized design, with six ganyong flour formulation treatments: soy flour (80: 0), (75: 5), (70:10), (65:15), (60:20), and (55:25), then analyzed the levels of protein, texture, and characteristics of organoleptic as well as the proximate analysis of the best formulation. Levels of protein data and texture were analyzed using ANOVA followed by a further test HSD while organoleptic test data were analyzed using the Friedman test and Wilcoxon test. The results of the highest levels of protein is 18.91% at 55:25 formulation, the texture of the most violent is 2894.66 gf at 55:25 formulation. As an organoleptic cookies that has been substituted by ganyong flour and soy flour in a variety of treatments still can be acceptable organoleptic so the best cookies are cookies that has the highest levels of protein, at 55:25 of 18.91%, levels of ash 2.10%, levels of fat 10.15%, levels of water 3.6% and amounted to 65.24% carbohydrate.